Pengaruh Pemberian Bubur Kacang Hijau Terhadap Kadar Hemoglobin (Hb) Pada Wanita Usia Produktif Di PMB Teofani Muncar- Banyuwangi - Maya Dinda Arista; Sulistiyah Sulistiyah (Journal of Innovative and Creativity, 2025)
Anemia is a condition in which the level of hemoglobin (Hb) in the blood falls below the normal range and can occur in anyone. In Indonesia, anemia is largely caused by iron deficiency. Iron intake can be fulfilled through foods derived from both animal and plant sources. One plant-based food rich in iron is mung beans. This study aims to examine the effect of consuming mung bean porridge on increasing hemoglobin levels in women of reproductive age. The research employed a quantitative method with a pre-experimental design, specifically a one-group pretest-posttest design. The study population consisted of women of reproductive age who visited PMB Teofani Muncar, Banyuwangi. The sampling technique used was incidental sampling, resulting in 15 respondents who met the inclusion criteria. Data were analyzed using the Wilcoxon test as a non-parametric bivariate analysis, due to the data not being normally distributed. The test results showed a p-value of 0.003, which is lower than the significance threshold of 0.05. These findings indicate a statistically significant difference in hemoglobin levels before and after the intervention. It can therefore be concluded that the consumption of mung bean porridge has a positive effect on increasing hemoglobin levels in women of reproductive age. Thus, mung bean porridge can serve as an effective, locally based nutritional intervention to help prevent and manage anemia, particularly in women of reproductive age.